Readily Accessible Multiplane Microscopy: 3D Tracking the HIV‐1 Genome in Living Cells. (14th December 2015) - Itano, Michelle S.; Bleck, Marina; Johnson, Daniel S.; Simon, Sanford M.
Abstract : The trafficking of human immunodeficiency virus (HIV)‐1 genomic RNAs from sites of replication in the nucleus, through the cytoplasm, to sites of assembly at the plasma membrane is critical for HIV‐1 viral replication. We present a broadly accessible microscopy method that captures multiple focal planes simultaneously, enabling high‐resolution 3D imaging of a single macromolecule. We show that HIV‐1 genomic RNAs are most mobile in the cytosol, and undergo confined mobility at sites along the nuclear envelope and in the nucleus and nucleolus. Abstract : Human immunodeficiency virus (HIV)‐1 infection and the associated disease AIDS are a major cause of human death worldwide with no vaccine or cure available. The trafficking of HIV‐1 RNAs from sites of synthesis in the nucleus, through the cytoplasm, to sites of assembly at the plasma membrane are critical steps in HIV‐1 viral replication, but are not well characterized. Here we present a broadly accessible microscopy method that captures multiple focal planes simultaneously, which allows us to image the trafficking of HIV‐1 genomic RNAs with high precision. This method utilizes a customization of a commercial multichannel emission splitter that enables high‐resolution 3D imaging with single‐macromolecule sensitivity. We show with high temporal and spatial resolution that HIV‐1 genomic RNAs are most mobile in the cytosol, and undergo confined mobility at sites along the nuclear envelope and in the nucleus and nucleolus. These provide important insights regarding the mechanism by which the HIV‐1 RNA genome is transported to the sites of assembly of nascent virions.